A Better Model? An Empirical Investigation of the Fama–French Five‐factor Model in Australia*. (20th September 2016) - Chiah, Mardy; Chai, Daniel; Zhong, Angel; Li, Song
Abstract: Recently, Fama and French (2015a ) propose a five‐factor model by adding profitability and investment factors to their three‐factor model. This model outperforms the three‐factor model previously proposed by Fama and French (1993 ). Using an extensive sample over the 1982–2013 period, we investigate the performance of the five‐factor model in pricing Australian equities. We find that the five‐factor model is able to explain more asset pricing anomalies than a range of competing asset pricing models, which supports the superiority of the five‐factor model. We also find that despite the results documented by Fama and French (2015a ), the book‐to‐market factor retains its explanatory power in the presence of the investment and profitability factors. Our results are robust to alternative factor definitions and the formation of test assets. The study provides a strong out‐of‐sample test of the model, adding to the comparative evidence across international equity markets.